Inclusiveness public research - Jadi Suriadi (Jurnal Kewidyaiswaraan, 2021)
Abstract It had identifed clearly in working of research methodology, there are alot of certain aspects, variables or elements in social science or humanity under dynamic, multipolarrecyprocal causality and in a complex condition. Therefore approching to qualitative or quantitative methodology require enrichment with empirical aproach, especially people involvement. The researhed need to run and to configure inclusiveness, This research aim to explore using of wellbeing methodology (WM) approach, to implemen social research, whit a case study named as ICB.. the research gap to be identified, are: 1) is it possible to design an instrument of measurement tool to measure ICB?; 2) is the toll possible to implemented, to measrue ICB?; 3) may the outcome to transform to material of public education?Based on teoritical dan conseptual explanation, data exploration, explanation and certain detail measurement of peeception, partiipation and acceptability of people, the answers are a proof. Yes, there are. the hyphoteses are solved in qualitative approach. Furtherfor, ther are 6 variables and 18 significancy hiphoteser to confogure scorring of perception, participation and acceptibility of people. With scale 9, and scor of significancy preference is, the data show that the scorring all bove. Meaning thtat all scor in significant condition. WM introduce a new perspective of approaching to capture closed reality of research object, in term of index of county brandinng (ICB). In certain conceptual, logic order and procedure, WM can be implemented widely, such as IDG/s issue.